MYC overexpression leads to increased chromatin interactions at superenhancers and MYC binding sites - See, Yi Xiang (2022)
The MYC oncogene encodes for the MYC protein and is frequently dysregulated across multiple cancer cell types, making it an attractive target for cancer therapy. MYC overexpression leads to MYC binding at active enhancers, resulting in a global transcriptional amplification of active genes. Since superenhancers are frequently dysregulated in cancer, we hypothesized that MYC preferentially invades into superenhancers and alters the cancer genome organization. To that end, we performed ChIP-seq, RNA-seq, 4C-seq and SIQHiC (Spike-in Quantitative Hi-C) on the U2OS osteosarcoma cell line with tetracycline-inducible MYC. MYC overexpression in U2OS cells modulated histone acetylation and increased MYC binding at superenhancers. SIQHiC analysis revealed increased global chromatin contact frequency, particularly at chromatin interactions connecting MYC binding sites at promoters and enhancers. Immunofluorescence staining showed that MYC molecules formed punctate foci at these transcriptionally active domains after MYC overexpression. These results demonstrate the accumulation of overexpressed MYC at promoter-enhancer hubs and suggest that MYC invades into enhancers through spatial proximity. At the same time, the increased protein-protein interactions may strengthen these chromatin interactions to increase chromatin contact frequency. CTCF siRNA knockdown in MYC overexpressed U2OS cells demonstrated that removal of architectural proteins can disperse MYC and abrogate the increase in chromatin contacts. By elucidating the chromatin landscape of MYC driven cancers, we can potentially target MYC associated chromatin interactions for cancer therapy.